European States and the Euro / Europeanization, Variation, and Convergence - Dyson Kenneth (Oxford University Press, 2002)
This book examines the effects on public policies, political structures, discourses, and identities. Introduction: EMU as Integration and Europeanization and Convergence, European and Global Contexts, EMU's Integration and EMU and Monetary Governance in the European Union: The Political Economy of the ''Stability Culture'', The Political Economy of Fiscal Policy under Monetary Union, Domestic Political and Policy Contexts, Britain and EMU, EMU: A Danish Delight and Dilemma, The Italian State and the Euro: Institutions and Discourse and Policy Regimes, Sectors and States and EMU, Politics and Banks and Financial Market Governance in the Euro-Zone, The Euro and Labor Market and Wage Policies, Conclusions: European States and Euro Economic Governance, References, Index.